(untitled) (Research, Society and Development, 2022)
Siparuna guianensis Aubl., known as “negramina”, “capitu”, is a small tree used for headaches, colds, fevers, as a healing agent, insect, and tick repellents. This study aimed to evaluate the chemical composition and seasonal variability of essential oils from the leaves of S. guianensis. Botanical material was collected in Monte do Carmo, Tocantins, Brazil. The powder from the leaves was submitted to hydrodistillation in a Clevenger apparatus, and the identification of the compounds was performed by GC-MS. In volatile oils, 21.32% to 55.44% of sesquiterpenes, 19.95 to 49.73% of oxygenated sesquiterpenes, 0.48 to 1.55% of oxygenated monoterpenes, 0 to 5.67% of monoterpene hydrocarbons were identified, 0 to 48.2% of other compounds. The major compounds were γ-muurolene (13.99 to 35.97%), Curzerene (7.22-19.15%), Curzerenone (7.3-18.13%), 2-undecanone (3.99- 10.63%). The presence of two clusters was verified: cluster I, discriminated by the compounds Curzerenone, β-selinene, δ-elemene, corresponding to the months with the lowest index, and cluster II, discriminated by the β-burbonene, corresponding to the months with the highest index rainfall index. Comparing the present study with data from the literature, it is concluded that S. guianensis presents great chemical variability, which can be explained by genetic factors, seasonality, light, temperature, which can alter the production of metabolites. As S. guianensis has broad therapeutic potential as an antimicrobial and promising larvicidal activity, there is a need for agronomic studies to obtain specimens that require more interesting chemical components for the pharmaceutical industry. This study is the first carried out with oils from leaves collected in Monte do Carmo, Tocantins, Brazil.